Yield Indices for Meat in Pre-processing of Nemipterus japonicus (Bloch, 1791) - H.B., Pawar; M.M., Shirdhankar; S.K., Barve; S.B., Patange (Fishery Technology, 2025)
Nemipterus japonicus is preferred for production of surimi in India and in other Asian countries as the surimi produced from this fish is of high grade with white colour. The yield of processed or semiprocessed product in processing of this fish is a subject of prime importance. An attempt was made to establish relationships between meat yield and quantity of raw material used for processing, for facilitating appropriate managerial decision in surimi industry. Nemipterus japonicus specimens collected for the study were grouped in three length groups and were processed further with straight as well as inclined cut dressing style. The weight of scale, fin, head, meat and bone were recorded for both the dressing styles, and belly flap weight was additionally recorded for the straight cut dressing style. Average meat yield increased as the fish grew while the head weight decreased. The highest average meat yield recorded in 15-21 cm length group for straight cut and inclined cut were 50.57% and 52.10% respectively. The highest average head weight was recorded in 5-10 cm length group for straight cut (29.38%) and inclined cut (37.24%) dressing styles. Scale and other waste did not show increasing or decreasing trends with growth of N. japonicus. Nomographs were developed to predict the meat yield for various length groups as well as for pooled length group for both straight and inclined cut dressing styles.